English Language Skills for Islamic Economic Students: Expectation Versus Reality - Suwandi Suwandi (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Students of Islamic economics should be taught the English language with the goal of equipping them with the abilities necessary to successfully complete duties both in the classroom and in the workplace via this instruction. This study has a dual objective: first, to investigate the perspectives of both students and lecturers regarding the types of English language skills required for a major in Islamic Economics; and second, to determine whether the current English for Specific Purposes (ESP) course being offered is pertinent to what the students really require. The participants in this qualitative descriptive study included three lecturers and 219 students who were enrolled in the third and fifth semesters of the Islamic Economics Study Program at an Indonesian State Islamic University. The study was carried out by researchers using qualitative research methods. Two different methods were used to collect the data: an online survey that was broken up into two sections (one to investigate information related to the demographics of the student participants, and the other to investigate their perceived language skill needs), and an interview with the participants of the study who were lecturers. According to the findings, the instructors and the students do not have the same notions about the necessary linguistic abilities. The majority of students believed that the ability to speak and write were more essential than any other language abilities; nevertheless, the instructors placed greater emphasis on the ability to read and use proper grammar. This study recommends that the existing ESP syllabus be redesigned to meet the students’ needs.